Role of nasal decongestants in spontaneous healing of traumatic tympanic membrane perforation - Rai, Shiwani; Koirala, K.; Sharma, V. (Nepalese Journal of ENT Head and Neck Surgery, 2017)
Objective: To study the role of nasal decongestants in spontaneous healing of traumatic tympanic membrane perforation. Material and Methods: A prospective single blinded, randomized controlled study was carried out in the department of ENT, Manipal College of Medical Sciences, Pokhara, Nepal. Patients with traumatic tympanic membrane perforation were divided into two groups; those receiving nasal decongestants along with conservative measures (Group1) and those receiving conservative measures only (Group2). Healing of tympanic membrane was compared in between these groups at 1 and 3 months. Statistical analysis was done using SPSS 20. Results: There were 30 patients in group 1 and 28 patients in group 2. The mean age of the study population was 26.98 (SD= 7.53). The M: F ratio in group 1 was 0.58:1 and that in group 2 was 0.56:1. Complete healing was seen in 25 (83%) patients in group 1 and 16 (57.1%) patients in group 2 at the end of 1 month (P=0.029). Similarly, healing was seen in in 29 (96.7%) patients in group 1 and 21 (75%) patients in group 2 at the end of 3 months (P=0.023). Conclusion: Routine use of nasal decongestants increases the chances of spontaneous healing of traumatic tympanic membrane perforations.